2005
DOI: 10.1074/jbc.m413125200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Isoform of SK2 Assembles with Other SK Subunits in Mouse Brain

Abstract: The SK2 subtype of small conductance Ca 2؉ -activated K ؉ channels is widely distributed throughout the central nervous system and modulates neuronal excitability by contributing to the afterhyperpolarization that follows an action potential. Western blots of brain membrane proteins prepared from wild type and SK2-null mice reveal two isoforms of SK2, a 49-kDa band corresponding to the previously reported SK2 protein (SK2-S) and a novel 78-kDa form. Complementary DNA clones from brain and Western blots probed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 23 publications
4
79
1
Order By: Relevance
“…Consistent with distinct roles, disruption of any one of the SK genes does not result in altered expression levels of the other, intact genes (Bond et al, 2004). Nevertheless, heteromeric channels have been detected (Strassmaier et al, 2005), and overlapping functions cannot be discounted. Their central role in modulating local Ca 2ϩ transients and Ca 2ϩ -dependent events suggested that Ca 2ϩ -independent signaling mechanisms might modulate SK channels, perhaps by tuning their Ca 2ϩ sensitivity.…”
Section: Introductionmentioning
confidence: 68%
“…Consistent with distinct roles, disruption of any one of the SK genes does not result in altered expression levels of the other, intact genes (Bond et al, 2004). Nevertheless, heteromeric channels have been detected (Strassmaier et al, 2005), and overlapping functions cannot be discounted. Their central role in modulating local Ca 2ϩ transients and Ca 2ϩ -dependent events suggested that Ca 2ϩ -independent signaling mechanisms might modulate SK channels, perhaps by tuning their Ca 2ϩ sensitivity.…”
Section: Introductionmentioning
confidence: 68%
“…As a result of the multimeric assembly nature of SK channels, this leads to the possibility of heteromultimeric assembly in which more than one SK family member (SK1-3) may assemble into a given channel complex. This has been demonstrated in heterologous expression systems (1,17,20,26) and directly demonstrated in native tissue using immunoprecipitation (33). In addition, the transgenic expression of a dominant negative SK subunit supports the heteromultimeric assembly of SK channels in vivo (38).…”
Section: Discussionmentioning
confidence: 92%
“…164 In expression systems, both homomeric and heteromeric K Ca 2 channels are formed, 165,166 but the existence of heteromeric K Ca 2 channels has so far not been confirmed in native tissues. Similar to K Ca 1.1 channels, K Ca 2 channels can be alternatively spliced to generate channels with modified calmodulin binding as in the case of K Ca 2.1, 167 with an extended N-terminus dubbed SK2-L as in the case of K Ca 2.2, 168 or without the N-terminus and first transmembrane segment as in the case of K Ca 2.3. 169,170 Alternative splicing of K Ca 2.3 resulting in the insertion of fifteen additional amino acids in the outer pore region can also produce K Ca 2.3 channels, which are insensitive to the peptide toxins apamin and leiurotoxin-I.…”
Section: +mentioning
confidence: 99%